2015
DOI: 10.1111/vox.12273
|View full text |Cite
|
Sign up to set email alerts
|

Duffy blood group phenotype–genotype correlations using high‐resolution melting analysis PCR and microarray reveal complex cases including a new null FY*A allele: the role for sequencing in genotyping algorithms

Abstract: Both the high-resolution melting analysis and SNP microarray assays were concordant and showed genotyping, as well as phenotyping, is essential to ensure 100% accuracy for Duffy blood group assignments. Sequencing is important to resolve phenotype/genotype conflicts which here identified alleles, one novel, that carry silencing mutations. The risk of alloimmunisation may be dependent on this zygosity status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…We envisage that the genetic test could be conducted by clinical or commercial laboratories with DNA sampling being added to the current pre-treatment screening procedures for clozapine, which includes blood testing, once regulatory approval is in place. Recent studies suggest that current genotyping procedures for determining Duffy-null status are both robust and reproducible, and thus their implementation in the context of a clinical blood monitoring service should be straightforward 60,61 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We envisage that the genetic test could be conducted by clinical or commercial laboratories with DNA sampling being added to the current pre-treatment screening procedures for clozapine, which includes blood testing, once regulatory approval is in place. Recent studies suggest that current genotyping procedures for determining Duffy-null status are both robust and reproducible, and thus their implementation in the context of a clinical blood monitoring service should be straightforward 60,61 .…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the Duffy-null genotype is the main causal factor for the Duffynull phenotype (classically termed "Fy(a-b-)") 59,62 . Recent studies have shown that direct genotyping is the best available method to identify Duffy-null individuals in the context of neutropenia 60,61 , since in the isolated handful of reported cases with Duffy-null phenotype in the absence of the rs2814778 mutation, neutropenia is not observed 63 . A further challenge to using Duffy-null phenotyping arises from other ACKR1 mutations causing weak antigen expression which can mimic the Duffy-null phenotype causing serological ambiguity, resulting in misclassification of up to 3.5% of individuals depending on population 60,62,64 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it could be used for blood group genotyping for antigens encoded by the SNPs. It has been shown to be reliable for Duffy, Kidd, Diego, and Indian blood group genotyping . Compared with some low‐throughput genotyping methods, such as PCR–sequence‐specific primer and PCR‐RFLP, HRM is a simple, rapid, sensitive, and one‐step closed‐tube genotyping method and can also scan for novel variants within the target amplicon.…”
Section: Discussionmentioning
confidence: 99%
“…Data were analyzed and compared to NCBI RefSeqGene NG_007483.2 ( GYPB ) and AF090739 ( GYP*Mur ). Genotyping and zygosity testing was performed using polymerase chain reaction (PCR) high‐resolution melting (HRM) assay . RBCs from the patient and compatible donors were phenotyped using standard serologic techniques.…”
Section: Brief Methodsmentioning
confidence: 99%